QTL mapping of adult plant resistance to stripe rust in the Fundulea 900 × Thatcher RIL population - Xiaocui Yan; Huimin Zheng; Peipei Zhang; Gebrewahid Takele Weldu; Zaifeng Li; Daqun Liu (Czech Journal of Genetics and Plant Breeding, 2021)
Wheat stripe rust, caused by Puccinia striiformis Westend. f.sp. tritici Eriks (Pst), is one of the most important diseases of bread wheat worldwide. Breeding resistant wheat cultivars is the most economical, effective and environmentally friendly way for controlling wheat stripe rust in China. The Romanian wheat line Fundulea 900 showed good resistance to wheat stripe rust at the adult stage. The present study aimed to map the quantitative trait loci (QTLs) for stripe rust resistance in 176 F2:6 recombinant inbred lines (RIL) derived from the cross of Fundulea 900 × Thatcher. The RIL population was phenotyped for stripe rust (YR) severity at Mianyang in the Sichuan province and Baoding in the Hebei province in the 2016/2017 and 2017/2018 cropping seasons. SSR markers combined with a preferred screened group (PSG) analysis were used to identify the QTLs for stripe rust in the population. Three QTLs for stripe rust resistance were mapped on chromosomes 1AL, 7BL and 7DS, respectively. All three QTLs originated from Fundulea 900 and were detected in all the environments. The QTL on 7DS was provided by the known resistance gene Yr18/Lr34. The two QTLs on chromosomes 1AL and 7BL were explained by 9.2 to 21.5% and 5.1 to 10.1% of the phenotypic variance, respectively and might be new QTLs. The QTLs identified in the study and their closely linked markers can be used for marker-assisted selection (MAS) in wheat breeding programmes.